GUIDELINE FOR IMPROVING THE INSTRUCTIONAL LEADERSHIP OF GUIYANG PUBLIC UNIVERSITY TEACHERS - Junhua, Wu; Plagattong, Pinyapat; Suteeniran, Niran; Setkajorn, Sarayut; Wimuttipanya, Jittawisut (Journal of MCU Nakhondhat, 2024)
The objectives of this research were to 1) study the current situation of teaching leadership of Guiyang public university teachers in China 2) develop guidelines for improving the teaching leadership of Guiyang public university teachers. Yang Yang in China 3) Evaluate suitability and the possibility of guidelines for improving the teaching leadership of teachers at Guiyang State University in China, consisting of five aspects: 1) teaching skills, 2) interpersonal relationships, 3) self - spirituality, 4) Evaluation and decision making 5) Change and innovation. The population consists of 375 full-time lecturers at 12 public universities in Guiyang in China. The research instrument was a questionnaire with a consistency index of 1.00. The confidence value is .88, with statistics for data analysis including percentage, mean, and standard deviation. and content analysis. The results of the research found that the current guidelines for improving leadership teaching of Guiyang Public University teachers in all 5 areas are at a high level. The guidelines for improving the teaching leadership of Guiyang Public University include 36 measures in 5 areas, including 8 measures to promote teaching skills, 9 measures to promote interpersonal relationships, 6 measures to promote self - spirit, 6 measures to support evaluation and development. Decision making and 7 measures to support change and innovation The suitability and feasibility of the guidelines for improving the teaching leadership of Guiyang State University teachers in five areas are high. This means that the guidelines for improving the teaching leadership of Guiyang Teachers State University are appropriate and feasible.